Emerging applications of porphyrins in photomedicine - Huang, Haoyuan; Song, Wentao; Rieffel, James; Lovell, Jonathan F. (Frontiers in Physics, 2015)
Biomedical applications of porphyrins and related molecules have been extensively pursued in the context of photodynamic therapy (PDT). Recent advances in nanoscale engineering have opened the door for new ways that porphyrins stand to potentially benefit human health. Metalloporphyrins are inherently suitable for many types of medical imaging and therapy. Traditional nanocarriers such as liposomes, dendrimers and silica nanoparticles have been explored for photosensitizer delivery. Concurrently, entirely new classes of porphyrin nanostructures are being developed, such as smart materials that are activated by specific biochemicals encountered at disease sites. Techniques have been developed that improve treatments by combining biomaterials with photosensitizers and functional moieties such as peptides, DNA and antibodies. Compared to simpler structures, these more complex and functional designs can potentially decrease side effects and lead to safer and more efficient phototherapies. This review examines recent research on porphyrin-derived materials in multimodal imaging, drug delivery, bio-sensing, phototherapy and probe design, demonstrating their bright future for biomedical applications.